Toponimi Kampung Sarkanjut Nenggeng dan Cibudug dalam Persfektif Hermaneutik - Hadianto Hadianto (PANTUN: Jurnal Ilmiah Seni Budaya, 2020)
The naming of a village is not only based on geographical location, but also on the psychological character of the village. As in Leuwigoong Subdistrict, the naming of the village is from an oral tradition, namely "sasakala" or a legend about how the village was formed. The story is based on folklore which develops and is embedded in society so that it unconsciously becomes an attitude or behavior. The use of unusual words makes the village toponymy unique, funny and even ridiculous. In its development, several village names seemed unsuitable for use, and even embarrassed the residents. The name Kampung Sarkanjut was shortened to disguise the pornographic connotation of the word 'Sarkanjut' to 'SKJ'. This study applies Paul Ricoeur's hermeneutics, through three processes of cultural understanding, namely: (a) Understanding of the appreciation of symbols (language) towards thinking ideas, (b) Giving meaning by symbols and careful exploration of meaning, and (c) Thinking by using symbols as the starting point. Through the process of understanding Paul Ricoeur's hermeneutics, village toponymy represents a view of life or advice in living life. The use of the word "kuntung" as a symbol of the property which has been passed on from parents to their children is illustrated by the use of the bag ("kuntung") as a place to store small coins so that they are not scattered. The assets which are inherited will be the responsibility of the children and their descendants to be cared for and guarded for the next generation. Life is always connected with other people. Humans are obliged to maintain social relations among humans, to complement and benefit each other.Keywords: Toponymy, Sasakala, identity, hermeneutics